Strategies for enabling private sector-driven affordable urban housing in Abuja, Nigeria - Nwachukwu, Lilian Njideka (2024)
Despite replacing the government’s direct provision of housing with an enabled private-driven approach for over three decades, the housing deficit in Nigeria has continued to increase to a figure estimated to be between 17 million and 22 million units. Abuja, the Federal Capital of Nigeria alone accounts for 10% of this deficit despite the significant number of unoccupied houses in the city. This research investigated the reason behind this failure and proposed recommendations to address the issue. The data for this research was collected using multiple qualitative methods – phenomenology, case study, and workshop in a Generic Qualitative Inquiry (GQI) approach; thus, semi-structured interviews were administered in two stages to 13 participants comprising public and private stakeholders in the housing sector to characterise the problem and define the solutions. Structured questions were presented to another 18 participants for discussion in a workshop, and semi-structured interviews were administered to the case study project participants (the MFF and 11 residents of its estates). The research revealed that the persistent housing deficit is due to low investment in and poor access to affordable housing. It shows that poor operational framework, which manifests in poor funding of agencies charged with enabling the private-driven affordable housing is responsible for its poor performance. Therefore, the factors affecting the performance of private-driven affordable housing include administrative bottlenecks in facilitating the availability and registration of serviced land for developers, land speculation encouraged by poor funding of agencies and resulting in commercialised public land allocation, high transaction cost and registration of land resulting in poor choice of location for affordable housing to reduce cost, the Land Use Act (LUA) limitation of the powers of Federal government on land, which affects the spread of affordable housing efforts across the country, poor and delayed approval of loan arising from delay in processing and securing approval of land registration, poor access to NHF mortgages due to low income resulting in poor demand capacity, low investment in, and wrong conceptualisation of affordable housing to the detriment of end user housing need. These findings indicate the need for a decentralised housing system to maximise state and local government powers on land to facilitate affordable land for housing and for meeting end user housing needs, which vary across the country.